Clinical profile and management of perforation peritonitis in Bharatpur hospital, Nepal: A prospective study. (October 2022) - Neupane, Subita; Koirala, Dinesh Prasad; Kharel, Sanjeev; Silwal, Shirish; Yadav, Krishna Kumar
Abstract: Introduction: The most common surgical emergency in general surgery is perforation peritonitis. It is a serious condition with a mortality rate of up to 20%, and it is the third most common cause of surgical abdomen after appendicitis and intestinal obstruction. The aim of this study to discuss clinical profile and management of perforation peritonitis in a hospital in central Nepal. Methods: This prospective study was done for one year at Bharatpur Hospital, Chitwan Nepal. In our study, only patient above 15 years were included and those who were not fit for anesthesia and surgery were excluded. Most of the patient were diagnosed clinically supported by lab investigations and imaging like X-ray and ultrasonography of abdomen. The variables analyzed were the risk factors of the patient like smoking, alcohol, liver disease and previous abdominal surgeries. Results: The majority of the patients were in the age group 50–59 years in male and 40–49 years in female. Among sixty cases, 31 were female and 29 were male with Female: Male ratio of 1.06:1. The most common cause of perforation found was peptic ulcer compromising 88.3% (53 cases) followed by appendicular perforation accounting 8.3% (5 cases). Similarly, Tubercular perforation was found in 3.3%. Smoking was most common risk factor accounting 88.3%, followed by alcohol consumption (48.33%) while, 15% of patients had positive history of NSAIDs consumption. On imaging, 38.33% patient had air fluid level on X-ray and 78.33% had gas under diaphragm. On blood investigation, leukocytosis was found in 53.33% of patients, hyponatremia in 10% of patients and hypokalemia in 18.33% of patients. While on urine examination, albumin was found in 5% of patients. The repair of perforation along with omentopexy was done in 73.3% of patients while only repair was done in 15% of patients. Only 8.3% opted for appendectomy while a very few patients (3.3%) went for resection with anastomosis. The Postoperative complications found were wound infection (43.3%), paralytic ileus (18.33%), sepsis (15%), followed by electrolyte imbalance (11.6%), postoperative bowel obstruction (6.6%) and burst abdomen (1.6%). While, there were only 3 cases of mortality. Conclusions: Perforation peritonitis is a frequently encountered surgical emergency. Various factors like age, sex, duration, site of perforation, extent of peritonitis and delay in surgical intervention are associated with morbidity and mortality. A successful management depends upon early surgical intervention, source control and exclusive intraoperative peritoneal lavage. Highlights: Perforation Peritonitis is a serious condition with a mortality rate of up to 20%. Age, sex, duration, site of perforation, extent of peritonitis and delay in surgical intervention affect morbidity and mortality. Early surgical intervention, source control and exclusive intraoperative peritoneal lavage are solutions.